2021
DOI: 10.3390/cells10051243
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Evaluation of Thoracic Aortic Calcium and Their Relations with Cardiovascular Risk Factors in the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil)

Abstract: Thoracic aortic calcium (TAC) appears to be a subclinical marker of cardiovascular disease (CVD) and to predict cardiovascular (CV) mortality. However, studies on TAC use tomographic scans obtained for coronary artery calcium (CAC) score, which does not include the aortic arch. This study evaluates TAC prevalence in aortic arch (AAC), ascending (ATAC) and descending thoracic aorta (DTAC) and verify whether they are associated with the same CV risk factors. Cross-sectional analysis, including 2427 participants … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…Porcelain aorta is more common in the elderly population, with a study revealing the median age of 79 years 6 . Our patient was a 52‐year‐old female, and this early extensive calcification of the porcelain aorta and coronaries could be attributed to smoking and dyslipidemia, which are risk factors known to accelerate atherosclerosis and aortic calcification 7,8 . This case report shows that PCI is a valuable treatment option for multivessel coronary disease when surgical revascularization is not feasible.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Porcelain aorta is more common in the elderly population, with a study revealing the median age of 79 years 6 . Our patient was a 52‐year‐old female, and this early extensive calcification of the porcelain aorta and coronaries could be attributed to smoking and dyslipidemia, which are risk factors known to accelerate atherosclerosis and aortic calcification 7,8 . This case report shows that PCI is a valuable treatment option for multivessel coronary disease when surgical revascularization is not feasible.…”
Section: Discussionmentioning
confidence: 69%
“…6 Our patient was a 52-year-old female, and this early extensive calcification of the porcelain aorta and coronaries could be attributed to smoking and dyslipidemia, which are risk factors known to accelerate atherosclerosis and aortic calcification. 7,8 This case report shows that PCI is a valuable treatment option for multivessel coronary disease when surgical revascularization is not feasible. CABG or coronary artery bypass grafting involves cannulation and clamping of the diseased aorta, which can lead to embolization from the atheromatous heavily calcified aorta, increasing the risk of stroke and other thromboembolic complications.…”
Section: Discussionmentioning
confidence: 92%
“…However, prior studies summarized above conducted in other populations have shown the same direction of association. We did not have information on the calcium content in the aorta which has shown to increase arterial stiffness [37]. However, still is much unknown regarding the relationship between PWV and aortic calcification in the general population.…”
Section: Discussionmentioning
confidence: 96%
“…артериосклероз развивается в результате кальцификации медиального слоя сосудистой стенки и сопровождается повышением жёсткости сосудистой стенки, пульсового ад и развитием гипертрофии левого желудочка (глж) [3], что в конечном итоге способствует прогрессированию сердечной недостаточности [4]. артериосклероз наблюдается при хронической болезни почек (хбп), сахарном диабете (Сд) и артериальной гипертензии (аг) [5].…”
Section: Introductionunclassified